2019
DOI: 10.1155/2019/8148156
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Survival Outcomes of Lung Cancer: A Population-Based Study

Abstract: Purpose. Lung cancer has been the top-ranking cause of cancer deaths in Taiwan for decades. Limited data were available in global cancer surveillance regarding lung cancer epidemiology in Taiwan, and previous reports are outdated. Patients and Methods. This population-based cohort study extracted data of patients with lung cancer from the Taiwan National Health Insurance database and determined the lung cancer incidence and prevalence during 2002–2014. Histological subtypes were retrieved from the Taiwan Cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 30 publications
2
52
1
Order By: Relevance
“…Dikshit R et al [22] in their million death study opine that data for the National Cancer Registry programme were primarily obtained from the urban cancer registries, and were not representative of the rural areas where most Indians habituate. Lin H.T et al [23] estimated the overall survival rates of lung cancer by utilizing the Charlson Comorbidity index (CCI). In their study [23], it was found that lung cancer patients with CCI score ≤ 1 (28.7% of total cases) had a better 5-year survival rate (24.5% vs 14.2%) compared to those with a score ≥ 2 (71.3% of total cases).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dikshit R et al [22] in their million death study opine that data for the National Cancer Registry programme were primarily obtained from the urban cancer registries, and were not representative of the rural areas where most Indians habituate. Lin H.T et al [23] estimated the overall survival rates of lung cancer by utilizing the Charlson Comorbidity index (CCI). In their study [23], it was found that lung cancer patients with CCI score ≤ 1 (28.7% of total cases) had a better 5-year survival rate (24.5% vs 14.2%) compared to those with a score ≥ 2 (71.3% of total cases).…”
Section: Discussionmentioning
confidence: 99%
“…Lin H.T et al [23] estimated the overall survival rates of lung cancer by utilizing the Charlson Comorbidity index (CCI). In their study [23], it was found that lung cancer patients with CCI score ≤ 1 (28.7% of total cases) had a better 5-year survival rate (24.5% vs 14.2%) compared to those with a score ≥ 2 (71.3% of total cases). Cardwell et al [24] in their population-based lung cancer cohort, report a weak inverse association between statin usage and time to lung cancer-specific death (11% reduction, p = 0.09).…”
Section: Discussionmentioning
confidence: 99%
“…Lung cancer is the leading cause of cancer mortality worldwide with an overall five-year survival rate of less than 20% [ 1 , 2 ]. Notably, ~40% of lung cancer patients have metastasis at the time of diagnosis which is associated with increased morbidity and mortality [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, researchers have been made great progress in the diagnosis and treatment of lung cancer. However, lung cancer always ranks first in the number of cancer deaths every year, accounting for 18.4% of total cancer deaths in 2018 [ 3 ], and most of them are related to the metastasis of lung cancer. At the time of diagnosis, more than 60% of lung cancer patients have advanced stage or metastasis [ 4 ].…”
Section: Introductionmentioning
confidence: 99%